The perceived value of customers: Antecedents and its effect on word-of-mouth - Phuong-Linh Nguyen; Dinh-Quyet Phan; Nguyen Thi Uyen (Global Business & Finance Review (GBFR), 2024)
Purpose: This study aims to investigate the antecedents of the customer's perceived value, including multi-channel integration and brand equity, and the impact of the perceived value on word-of-mouth. Design/methodology/approach: A quantitative approach by PLS-SEM was used in the research. This paper conducted a survey of 414 respondents who are customers of retail firms in Vietnam. Findings: The research results illustrate the significant impact of multi-channel integration and brand equity on the perceived value of customers. The study also found that word-of-mouth is directly and positively influenced by the customer's perceived value. Research limitations/implications: Besides multi-channel integration and brand equity, other factors that may act as antecedents of the perceived value have not been recognized in the study. The study only focuses on the retail industry with a relatively small sample size which is a limitation of the sample representative. Originality/value: This study provides reliable evidence about the important role of building an integrated multi- channel system and nurturing brand equity to increase the perceived value in customer's minds. Additionally, the research reinforces the convincing evidence of the significant and positive relationship between the customer's perceived value and their positive word-of-mouth communication.
Keywords: 650; Perceived value; Word-of-mouth; Multi-channel integration; Brand equity